Estimation of GHG Emissions from Water Reclamation Plants in Beijing. (1st September 2016) - Fan, Yupeng; Bai, Yanying; Jiao, Wentao
ABSTRACT: : A procedure for estimating Greenhouse gas (GHG) emissions from a wastewater reclamation plant in Beijing was developed based on the process chain model. GHG emissions under two typical water reclamation treatment processes, the coagulation‐sedimentation‐filtration traditional process and advanced biological treatment process, were examined. The total on‐site GHG emissions were estimated to be 0.0056 kg/m 3 and 0.6765 kg/m 3 respectively, while total off‐site GHG emissions were estimated to be 0.3699 kg/m 3 and 0.4816 kg/m 3 . The overall GHG emissions were 0.3755 kg/m 3 under the type 1 treatment, which is much lower than that under the type 2 of 1.1581 kg/m 3 . Emissions from both processes were lower than that from the tap water production. Wastewater reclamation and reuse should be promoted as it not only saves the water resources but also can reduce the GHG emissions. Energy consumption was the most significant source of GHG emissions. Biogas recovery should be employed as it can significantly reduce the GHG emissions, especially under the type 2 treatment process. Considering the wastewater treatment and reclamation process as a whole, the type 2 treatment process has advantages in reducing the GHG emissions per unit of pollutant. This paper provides scientific basis for decision making.